Ethical practices on energy efficiency: Demographic variations among households in Selangor, Malaysia - Salina, Daud; Sabihah, Hitam; Wan Noordiana, Wan Hanafi; Maryam Jamilah, Asha’ari; Mariam, Abdul Majid; Wan Fadzilah, Wan Yusoff; Maisarah, Ahmad Sofi (GBMR, 2025)
Purpose: This study investigates the ethical practices concerning energy efficiency among households in Selangor, Malaysia, with a focus on demographic variations. Design/methodology/approach: Utilising a comprehensive survey method, the research examines how variables such as gender, age, monthly household income, education level, and monthly electricity bill influence energy efficient behaviours. Findings: The findings reveal significant differences in energy consumption patterns and ethical practices across various demographic groups. Male respondents show a high agreement with ethical practices in energy efficiency. Additionally, respondents with higher income and education levels are more proactive in adopting energy-saving practices. Furthermore, older adults and those with higher monthly electricity bills also demonstrate a strong commitment to ethical energy efficiency behaviours. Research limitations/implications: The study highlights the need for further research to explore the underlying reasons for demographic differences in energy efficiency practices and to assess the long-term impact of educational initiatives and policy frameworks. Practical implications: This research provides valuable insights for policymakers and stakeholders aiming to enhance energy efficiency and ethical practices among diverse household demographics in Selangor, Malaysia. Tailored educational initiatives and policy frameworks are essential for fostering a culture of sustainability. Originality/value: The study underscores the importance of demographic-specific strategies to promote ethical energy consumption, suggesting that tailored approaches can significantly improve energy efficiency behaviours across different demographic groups.